How Does the Canadian General Public Rate Moderate Alzheimer's Disease? - Tarride, Jean-Eric (SAGE-Hindawi Access to Research, 2011)
Objectives. The objectives of this study were to elicit health utility scores for moderate Alzheimer's disease (AD) using members of the general public. Methods. Five-hundred Canadians were chosen randomly to participate in a telephone interview. The EQ-5D was administered to estimate the health utility score for respondents' current health status (i.e., no AD) and for a hypothetical moderate AD health state. Regression analyses were conducted to explain the perceived utility decrement associated with AD. Results. The mean age of the respondents was 51 years, 60% were female, and 42% knew someone with AD. Respondents' mean EQ-5D scores for their current health status and a hypothetical moderate AD were 0.873 (SD: 0.138) and 0.638 (SD: 0.194), respectively (P < 0.001). Age, gender, and education were significant factors explaining this decrement in utility. Conclusion. Members of the general public may serve as an alternative to patients and caregivers in the elicitation of health-related quality of life in AD.